Concepts of biochemistry for medical students - L.M., Srivastava ([S.l.] : CBS Publisher & Distributors P Ltd, 2011)
This book has been written through the aegis of National BookTrust of India under the scheme forCore Books on Medical Sciences Project.One of the significant features of the book has been that the chapters have been written by thefaculty members of the medical institutions who themselves have expertise on the topic and are very actively engaged in teaching of medical students and conducting clinical research. Although this book would be primarily catering for the medical students at pre-clinical stage yet it would also be useful to others at the para-clinical and clinical phases of the medical education. This book comprises the text pertaining to the basic aspects of the biochemistry which has been well interpreted and illustrated vis-a-vis health and disease and hence would be of paramount interest to both the medical students and teachers. In addition to covering the core subject areas of the medical syllabus inclusion of Human Genome Project; Oxidant and antioxidant states in health and disease: and Biochemical basis of environmental health hazards in the text would keep the medical as well as general biology students well aware of the present day knowledge and progress in biochemistry.
Keywords: medicine,biochemistry